(untitled) (UNED Research Journal, 2011)
The dove Streptopelia decaocto is a Palearctic species that has become established in Mexico. Leucism is a partial loss of pigmentation. Here, we report the first leucistic individual of this dove, from El Rosario de Abajo, Ensenada, Baja California, Mexico, November 29th, 2009 (30°02’24” N y 115°44’24” W).